Deciphering growth abilities of fusarium oxysporum f. sp. pisi under variable temperature, pH and nitrogen - Chakrapani, Kota; Chanu, W. Tampakleima; Sinha, Bireswar; Thangjam, Bijeeta; Hasan, Wajid; Devi, Konjengbam Sarda; Chakma, Tusi; Phurailatpam, Sumitra; Mishra, Lokesh Kumar; Singh, Gopi Mohan; Khoyumthem, Pramesh; Saini, Rahul (Frontiers in Microbiology, 2023)
Fusarium wilt caused by Fusarium oxysporum f. sp. pisi (Fop) is an important disease and major obstacle to pea production, causing huge losses to growers. The focus of this study was on isolation followed by morphological, molecular characterization and analyzing the growth of the casual agent under variable temperature, pH and Nitrogen levels. The morphological features of radial growth, sporulation, pigmentation and mycelial characterization were examined and the variability of all isolates was presented. Molecular characterization of the fungus by ITS rDNA sequencing revealed that all 13 isolates belong to Fusarium oxysporum species. Six isolates were tested for temperature, pH and nitrogen dosage optimization studies. Seven different temperatures, viz., 21, 23, 25, 27, 29, 31, 33 °C and pH values, having 3,4,5,6,7,8 and 9 pH, as well as nitrogen dosage levels of 0 g, 3 g, 5 g, 7 g, 9 g, 11 g and 13 g were tested against all six isolates, respectively. The results showed that all isolates exhibited the highest growth at a temperature of 25 °C and the optimal temperature range for growth of Fusarium oxysporum was 23-27 °C. All isolates showed the highest growth at pH 5. Change in the nitrogen doses of the base ended in formation of thick, dense, fluffy mycelium of the casual agent. Six isolates were used for combination studies with seven different levels of temperatures, pH levels and nitrogen dosages. The density plots revealed the variations in the growth of the isolates with changes in temperature, pH and nitrogen levels, which can lead to mutations or genetic changes in the pathogens that could potentially introduce new threats to pea cultivation.